Perceptions of the value of Collective Worship amongst trainee teachers in England - Mogra, Imran (Journal of beliefs and values, 2016)
This article draws on a survey conducted with primary school trainee teachers in a university in England. The survey set out to investigate their knowledge, understanding and their view about the role that Collective Worship (CW) plays in schools. A sample of 125 participants contributed to the findings of this inquiry by completing a questionnaire. The results demonstrate that these students think that CW makes a significant contribution to the spiritual, moral, social, cultural (SMSC), and emotional and intellectual development of pupils. The most significant finding is that they think worship should be retained. Their views are important as they provide further insights for the debates currently taking place about the status and nature of worship in schools. The research has implications for further studies and to develop the overall knowledge about CW among trainee teachers.